Pengaruh Pertumbuhan Laba dan Kualitas Audit terhadap Kualitas Laba - Ghoni, Jakfar Akbar Ghoni; Tumirin, Tumirin (Universitas Muhammadiyah Gresik, 2025)
Abstrak This studiy aims to examine the effect to profit growth and audit quality in metal & allied products sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021 which are listed on the Indonesia Stock Exchange (IDX). This study uses a descriptive research type with a quantitative approach, which is measured using a multiple linear regression-based method with SPSS 22.00. The population of this study is metal & allied products sub-sector manufacturing companies listed on the Indonesi Stock Exchange (IDX) for the period 2018 to 2021. The sample was determined based on the purposive sampling method, with a sample size of 15 metal & allied products sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021, so that the total observations in this study were 120 observations. The results of the study prove that based on the results of the study, profit growth and audit quality have a partial effect on profit quality.